Genotoxic and Mutagenic Assessment Induced by Vinasse, Before and After Being Subjected to Bio-oxidation and Fenton Processes. - Iván Meléndez Gélvez; Diego Alberto Salazar Moncada; Elkín Johan Granados Vega; Jennifer Carolina Soledad Maldonado; Carlos Alberto Peláez Jaramillo (Vitae)
Background: Colombia is joining global initiatives to mitigate climate change through bioethanol production, as it has large sugar cane plantations and sugar mills, particularly in the Valle del Cauca region. One of the main by-products of the bioethanol industry is vinasse, which consists mainly of water, organic solids and heavy metals. Some of the compounds present in vinasses, such as melanoidins and phthalates, show genotoxic, mutagenic and carcinogenic activity in onion cells, tilapia and aquatic organisms. Various methods, such as bio-oxidation and Fenton reaction, have been used to reduce the organic load of vinasses. Among the most commonly used assays to study genotoxicity and mutagenicity are single cell gel electrophoresis (comet assay) and the Ames test. Objective: In this study, the genotoxicity in human lymphocytes and the mutagenicity in Salmonella typhimurium induced by different dilutions of vinasse produced at the bioethanol production plant in Frontino, Antioquia, before and after being subjected to biooxidation and Fenton processes, were evaluated. Methods: Genotoxicity was evaluated by the comet assay in human lymphocytes, and mutagenic activity was evaluated by the Ames test using Salmonella typhimurium strains TA98 and TA100, with and without the addition of microsomal enzymes (S9). Both tests were applied to each type of vinasse considered in this study, including raw vinasse (RV), bio-oxidised vinasse (BV) and Fenton oxidised vinasse (FV). Results: The results showed that at RV doses above 3%, viability decreased to values between 70% and 88%, whereas for BV and FV, viability remained above 93% and 94%, respectively. Vinasse was also found to have a dose-dependent effect on genotoxicity. However, no mutagenic activity was observed in any of the Salmonella strains evaluated, indicating that vinasse does not induce mutations. Conclusion: The importance of addressing vinasse pollution and treatment methods to reduce its toxicity is emphasised. However, further research is needed to fully understand the risks associated with vinasse exposure and to develop effective mitigation strategies.